DETERMINATION OF WATER POLLUTION USING SATELLITE DATA - Kaļva, Lilita; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
One of the major eutrophication - causing substances are all elements - phosphorus and nitrogen, which enters the surface water from agricultural areas, sewage treatment plants and other sources. Therefore, the more attention focused on the nutrient elements –phosphorus and nitrogen effects on algal growth and weight gain. In Rezekne Technology academy laboratory experiments were carried out under laboratory conditions, the algae, grown in weight gain, depending on the water temperature and nutrient concentration. Lake Burtnieks is analyzed with satellite data. The results shows that satellite data can be used for remote monitoring of bodies of water quality change and water quality forecasting.